2021
DOI: 10.3390/ph14030175
|View full text |Cite
|
Sign up to set email alerts
|

The Angiotensin II Type 2 Receptor, a Target for Protection and Regeneration of the Peripheral Nervous System?

Abstract: Preclinical evidence, accumulated over the past decade, indicates that the angiotensin II type 2 receptor (AT2R) stimulation exerts significant neuroprotective effects in various animal models of neuronal injury, notably in the central nervous system. While the atypical G protein-coupled receptor superfamily nature of AT2R and its related signaling are still under investigation, pharmacological studies have shown that stimulation of AT2R leads to neuritogenesis in vitro and in vivo. In this review, we focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…The high abundance of this receptor is also transiently expressed in rodent fetus, suggesting that Ang II could have a role in the AT2 receptor during development and cell differentiation [ 36 ]. For example, activation of this receptor can induce neurite formation and neuronal differentiation in vitro from rat pheochromocytoma cell line PC12W and fetal rat neurons [ 9 , 37 ] , revin [ 38 ]. In humans, mutations of the AT2 receptor have been found in female or male patients with mental retardation and have been implicated in brain development and maturation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high abundance of this receptor is also transiently expressed in rodent fetus, suggesting that Ang II could have a role in the AT2 receptor during development and cell differentiation [ 36 ]. For example, activation of this receptor can induce neurite formation and neuronal differentiation in vitro from rat pheochromocytoma cell line PC12W and fetal rat neurons [ 9 , 37 ] , revin [ 38 ]. In humans, mutations of the AT2 receptor have been found in female or male patients with mental retardation and have been implicated in brain development and maturation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Components of the renin-angiotensin system (RAS) have been previously reviewed or discussed extensively [19,24,[58][59][60][61][62][63][64]. Nevertheless, the main findings are briefly summarized here for an overview.…”
Section: Endogenous Angiotensin Ligands and Angiotensin Receptorsmentioning
confidence: 99%
“…Accumulating evidence has proven that drugs affecting the renin-angiotensin system can modulate pain transmission [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Recent studies have also shown that drugs mimic or antagonize angiotensin type 1 and 2 (AT1R and AT2R) receptor-mediated actions do produce a beneficial analgesic effect in rodent models of chronic pain types [17,20,22,28,29,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the RAS components are known to be expressed into the sensory nervous system, tending to demonstrate the presence of a local RAS in the peripheral nervous system ( Bessaguet et al, 2016 ). Various preclinical studies have highlighted the involvement of RAS modulation by the use of ACE inhibitors or angiotensin receptor blockers, in neuroprotection and pain control ( Gallinat et al, 1998 ; Lucius et al, 1998 ; Patil et al, 2010 ; Pavel et al, 2013 ; Kaur et al, 2015 ; Yuksel et al, 2015 ; Bessaguet et al, 2017 ; Danigo et al, 2021 ). Modulation of RAS was neuroprotective in rodent models of traumatic nerve injury like chronic constriction injury and sciatic nerve transection, as well as in rodent models of diabetic neuropathy or toxic neuropathy (CIPN) ( Oltman et al, 2008 ; Kaur et al, 2015 ; Yuksel et al, 2015 ; Bessaguet et al, 2017 ; Kim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%